2005
DOI: 10.1158/1541-7786.mcr-04-0178
|View full text |Cite
|
Sign up to set email alerts
|

A Nonclassic CCAAT Enhancer Element Binding Protein Binding Site Contributes to α-Methylacyl-CoA Racemase Expression in Prostate Cancer

Abstract: A A A-Methylacyl-CoA racemase (AMACR), an enzyme involved in branched-chain fatty acid B B B-oxidation that is normally expressed at high levels in human liver, is specifically and consistently overexpressed at both mRNA and protein levels in human prostate cancer and potentially other cancer types. To characterize the mechanisms underlying transcriptional regulation of AMACR at the genetic and epigenetic levels, we performed a series of methylation and reporter assays in prostate cancer tissues and cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Two CGIs were identified flanking the transcription start site (Figure 2A). The first is a novel CGI located upstream of the ATG site (−230 to −60; the position of the translation start site was set as +1) with 18 CG dinucleotides, whereas the second CGI downstream of the ATG site (48 to 357, not shown in Figure 2A) has been reported and shown to not be involved in gene regulation in PCa cells [5]. In concordance, our pilot studies indicated that the downstream CGI exhibited no differences in methylation/deletion/mutation status among the histological entities of the colon (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two CGIs were identified flanking the transcription start site (Figure 2A). The first is a novel CGI located upstream of the ATG site (−230 to −60; the position of the translation start site was set as +1) with 18 CG dinucleotides, whereas the second CGI downstream of the ATG site (48 to 357, not shown in Figure 2A) has been reported and shown to not be involved in gene regulation in PCa cells [5]. In concordance, our pilot studies indicated that the downstream CGI exhibited no differences in methylation/deletion/mutation status among the histological entities of the colon (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Since most malignancies increase fatty acid utilization as an energy source to fuel growth [2], it has been suggested that increased β-oxidation of branched-chain fatty acids provides transformed cells with a unique metabolic advantage [3]. This idea is supported by recent findings that knockdown of AMACR transcripts or inhibition of the racemase activity effectively blocked growth of prostate cancer (PCa) cells [4],[5]. In humans, the major sources of phytol-derived, 2-methyl-branched fatty acids are dietary ruminant fats, meat, and dairy products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, involvement of alterative regulatory mechanisms was likely in a subset of myxofibrosarcomas, because approximately 40% of AMACR-overexpressing myxofibrosarcomas lacked gene amplification. Actually, the expression level of AMACR in common carcinomas is mostly regulated by various transcriptional factors, such as C/EBP family members, Sp1, and ZNF202 (25)(26)(27). In the multivariate analysis of a subset cohort, AMACR overexpression, independent of SKP2, remained as the single adverse prognosticator, with an insignificant trend between two oncoproteins in expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…A number of early studies revealed this to be false, with AMACR expression in prostate cancer being a largely androgen-independent process [50,51]. Recent studies have identified a non-classical C/EBP binding site within the AMACR promoter region [52]. This binding site, located at the −80 bp position, has been shown to be responsible for the observed expression of AMACR in the normal liver and prostatic cancer-derived cell lines.…”
Section: Discussionmentioning
confidence: 99%